Voriconazole-induced Periostitis Following Lung Transplantation: Case Series - Gouji Toyokawa; Miho Yamaguchi; Takafumi Yamaya; Mitsuaki Kawashima; Chihiro Konoeda; Koh Okamoto; Masaaki Sato (Transplantation Reports)
Voriconazole, the first-choice treatment for invasive aspergillosis, can induce periostitis. For unknown reasons, most reports on this rare side effect are in the field of organ transplantation, especially lung transplantation, and mostly from Western countries. However, in Asian countries, including Japan, the incidence of this complication may be underestimated. Herein, we report three Japanese patients who developed voriconazole-induced periostitis after lung transplantation. The patients’ initial symptoms were pain in the left shoulder, bilateral axillae, and left upper arm. The duration of voriconazole treatment before symptom onset ranged from 5 to 59 months. The diagnosis was confirmed by bone scintigraphy in two patients and computed tomography scan in one patient with or without elevation of alkaline phosphatase levels. All three patients experienced symptom relief within 7 days of voriconazole discontinuation, and the bone scintigraphy findings and alkaline phosphatase elevation were reversible.